Outcome measures used in clinical research evaluating prehospital blood component transfusion in traumatically injured bleeding patients: A systematic review. Issue 6 (December 2021) - Tucker, Harriet; Avery, Pascale; Brohi, Karim; Davenport, Ross; Griggs, Joanne; Weaver, Anne; Green, Laura
Abstract : BACKGROUND: Trial outcomes should be relevant to all stakeholders and allow assessment of interventions' efficacy and safety at appropriate timeframes. There is no consensus regarding outcome measures in the growing field of prehospital trauma transfusion research. Harmonization of future clinical outcome reporting is key to facilitate interstudy comparisons and generate cohesive, robust evidence to guide practice. The objective of this study was to evaluate outcome measures reported in prehospital trauma transfusion trials. METHODS: Data Sources, Eligibility Criteria, Participants, and Interventions We conducted a scoping systematic review to identify the type, number, and definitions of outcomes reported in randomized controlled trials, and prospective and retrospective observational cohort studies investigating prehospital blood component transfusion in adult and pediatric patients with traumatic hemorrhage. Electronic database searching of PubMed, Embase, Web of Science, Cochrane, OVID, clinical trials.gov, and the Transfusion Evidence Library was completed in accordance with Preferred Reporting Items for Meta-analyses guidelines. Study Appraisal and Synthesis Methods Two review authors independently extracted outcome data. Unique lists of salutogenic (patient-reported health and wellbeing outcomes) and nonsalutogenic focused outcomes were established. RESULTS: A total of 3, 471 records were identified. Thirty-four studies fulfilled the inclusion criteria: 4 military (n = 1, 566 patients) and 30 civilian (n = 14, 398 patients), all between 2000 and 2020. Two hundred twelve individual non–patient-reported outcomes were identified, which collapsed into 20 outcome domains with varied definitions and timings. All primary outcomes measured effectiveness, rather than safety or complications. Sixty-nine percent reported mortality, with 11 different definitions. No salutogenic outcomes were reported. CONCLUSION: There is heterogeneity in outcome reporting and definitions, an absence of patient-reported outcome, and an emphasis on clinical effectiveness rather than safety or adverse events in prehospital trauma transfusion trials. We recommend stakeholder consultation and a Delphi process to develop a clearly defined minimum core outcome set for prehospital trauma transfusion trials. LEVEL OF EVIDENCE: Scoping systematic review, level III. Abstract : Supplemental digital content is available in the text.